2009
DOI: 10.1016/j.bpj.2009.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and Crowding Effects in the Aggregation of a 10-Residue Fragment Derived from Islet Amyloid Polypeptide

Abstract: Fibril formation from amyloidogenic peptides is a hallmark of a wide range of diseases, including Alzheimer's disease and type II diabetes. Characterization of the aggregation process should include intrinsic factors, such as sequence variation, and extrinsic factors, such as crowding effects. To this end, we examined the interactions of dimers composed of residues 20-29 of human islet amyloid polypeptide (hIAPP), which form fibrils in vitro, and the nonamyloidogenic rat IAPP (rIAPP) using molecular dynamics s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
42
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 29 publications
6
42
1
Order By: Relevance
“…It is possible that the early β-sheets are limited to residues 23-27, which would be consistent with early fragment studies showing that hIAPP [23][24][25][26][27] is the smallest fragment of hIAPP capable of forming amyloid fibrils (15). However, the hIAPP 22-27 fragment aggregates 40 times faster than hIAPP [23][24][25][26][27] and hIAPP [20][21][22][23][24][25][26][27][28][29] aggregates faster still, suggesting that the oligomeric β-sheets might extend beyond our labeled region to include the serines (15). Nonetheless, we know that the β-sheets must be small because, like typical random coil peptides, the unlabeled region of the spectra has only a minimal peak at 1,620 cm −1 (and does not extend to V17 or G33).…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…It is possible that the early β-sheets are limited to residues 23-27, which would be consistent with early fragment studies showing that hIAPP [23][24][25][26][27] is the smallest fragment of hIAPP capable of forming amyloid fibrils (15). However, the hIAPP 22-27 fragment aggregates 40 times faster than hIAPP [23][24][25][26][27] and hIAPP [20][21][22][23][24][25][26][27][28][29] aggregates faster still, suggesting that the oligomeric β-sheets might extend beyond our labeled region to include the serines (15). Nonetheless, we know that the β-sheets must be small because, like typical random coil peptides, the unlabeled region of the spectra has only a minimal peak at 1,620 cm −1 (and does not extend to V17 or G33).…”
Section: Resultssupporting
confidence: 68%
“…Early work revealed a correlation between the ability to form amyloid in vitro and the sequence in the 20-29 region (13,14). The fragment hIAPP [20][21][22][23][24][25][26][27][28][29] (SNNFGAILSS) readily forms amyloid fibrils, as do smaller fragments such as hIAPP 23-27 (13-17) and hIAPP [21][22][23][24][25][26][27] ; the latter has been characterized with X-ray crystallography (5). Molecular dynamics simulations corroborate the assembly of such fragments into β-sheet structures (18)(19)(20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the significantly prolonged lag time of the control analog 20K-hIAPP (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) suggested that the positive charge and/or the bulky side-chain may place a barrier to the assembly of amyloid aggregates. The oligomerization states of IAPP and related fragments have been studied mostly by molecular dynamics simulation and experimental evidence is still necessary [29][30][31]. The present gel filtration study revealed different oligomerization properties of fragments of hIAPP and pIAPP.…”
Section: Discussionmentioning
confidence: 75%
“…In support of this idea, a recent study on hIAPP and rIAPP demonstrated that the aggregation-prone hIAPP forms intramolecular b-turn more readily than rIAPP [34]. Techniques including X-ray fiber diffraction, electron diffraction, cryo-EM, FTIR, solid-state NMR and molecular dynamics simulations have been intensively applied to determine the fibril structure of hIAPP fragments, for example hIAPP (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), hIAPP (21)(22)(23)(24)(25)(26)(27), hIAPP (28)(29)(30)(31)(32)(33) [20,[35][36][37], with all results suggesting that the amyloidogenic region 20-29 adopts a steric zipper structure and further forms the cross-b spine of hIAPP amyloid [38]. Based on these observations, we proposed a possible amyloid-resistance mechanism for pIAPP in which the formation of stable dimers prevents peptides from further assembling into the bturn structure and also the formation of the following nucleus and ordered mature fibrils (Fig.…”
Section: Discussionmentioning
confidence: 99%